2022
DOI: 10.1002/mdc3.13560
|View full text |Cite
|
Sign up to set email alerts
|

Tremor and Movement Slowness Are Two Unrelated Adverse Effects Induced by Valproate Intake

Abstract: Background To date, only a few clinical and neurophysiological studies have assessed the features of valproate‐induced tremor (VIT), and whether valproate (VPA) affects voluntary movements is underinvestigated. Objective To better characterize the clinical and neurophysiological features of VIT in patients with epilepsy and the effect of VPA on the execution of voluntary movement. Methods We tested 29 patients with VIT (13 taking VPA alone and 16 taking VPA plus other antiepileptics). Patients underwent a neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Additionally, various studies have highlighted associations between degenerative cerebellar disease, cerebellar tumours, ischemic lesions, and movement slowness in ET [3]. Further supporting the role of the cerebellum in altered voluntary movement execution, we have recently demonstrated that patients with tremor induced by valproate may also present movement slowness which re ect a cerebellar network disruption due to valproate [37]. Moreover, cerebellar dysfunction may give rise to various cognitive dysfunctions, including the Cognitive Affective Cerebellar Syndrome (CCAS), as postulated by Schmahmann et al in the '90s.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Additionally, various studies have highlighted associations between degenerative cerebellar disease, cerebellar tumours, ischemic lesions, and movement slowness in ET [3]. Further supporting the role of the cerebellum in altered voluntary movement execution, we have recently demonstrated that patients with tremor induced by valproate may also present movement slowness which re ect a cerebellar network disruption due to valproate [37]. Moreover, cerebellar dysfunction may give rise to various cognitive dysfunctions, including the Cognitive Affective Cerebellar Syndrome (CCAS), as postulated by Schmahmann et al in the '90s.…”
Section: Discussionsupporting
confidence: 70%
“…Re ective markers were strategically placed on the dominant hand, and on the distal phalanx of the index nger and thumb. We recorded postural tremors in two different arm positions: arms outstretched in front of the chest (Posture 1 -P1) and arms exed at the elbows in a lateral "wing beating" posture (Posture 2 -P2) [8, 5,7,37,6,4,39,40]. Three 45-second recordings were obtained for each position.…”
Section: Kinematic Recordings and Analysismentioning
confidence: 99%
See 3 more Smart Citations